Fifa 11+ Warm-up Terhadap Peningkatan Speed pada Pemain Sepak Bola - Agustiyawan Agustiyawan; Sri Yani; Heri Wibisono (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify the effect of fifa 11+ warm-up on speed increase in football player Methods: This article This study uses a quasi-experimental research method with measurements carried out before and after treatment with a pre-test and post-test without control group designed to determine the effect of FIFA 11+ warm-up on increasing speed in soccer players. FIFA 11+ warm-up for 45 minutes in 4 weeks. Measurement of speed with a 20 meter sprint test conducted before and after the FIFA 11+ warm-up  Results: The results showed that before the FIFA 11+warm-up was practiced, the average speed (pre) was 3,50 ± 0,177 second, while the average speed after the pursed lips breathing (post) method was 3,29 ± 0,246 second. The results of the parametric paired t test show p value = 0.000, because p < 0.05 then Ho is rejected. The concluded that there is an effect of FIFA 11+ warm-up on speed increase in football player Conclusion:  The concluded that there is an effect of FIFA 11+ warm-up on speed increase in football player